Light as a Limiting Factor for Epilithic Algae in the Supralittoral Zone of Littoral Caves - Mayer, Danielle; Dubinsky, Zvy; Iluz, David (Frontiers in Marine Science, 2016)
In a littoral cave system, abiotic environmental properties, such as the intensity and spectral distribution of light, often change going from the exterior to the interior part of the cave, filtering the light and thus creating a deep-sea irradiance setting for marine flora. In this mini-review, we suggest that the supralittoral zone in littoral caves might provide a sanctuary for mesophotic calcifying algae. These abiotic conditions offered an opportunity for normally deep-water mesophotic species to expand their range due to their competitive advantage over shallow, open-water species. Supralittoral calcifying algae are significant for marine biodiversity but are likely to be damaged in the future by ocean acidification. We have summarized important abiotic factors regarding algae settlement and succession processes in the supralittoral zone of littoral caves, including their photosynthetic pigments and habitat requirements. We describe their zonation according to irradiance, and review previous research on epilithic alga¬¬l assemblages in littoral caves. Although we found a great deal of information on the algae of sea caves and littoral caves, no such information was published on the algae of the supralittoral zone of these caves. Nevertheless, some of the studies cited in this review have already set a good conceptual and methodological basis for the ecological research of the supralittoral algal flora of littoral caves.